DETERMINANTS OF PNEUMONIA INCIDENCE IN TODDLERS - Elda Satria; Fera Meliyanti; Fera Novitry (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Pneumonia is an acute lung infection caused by viruses, bacteria, fungi, and parasites. The most cases occurred in Tegal Rejo Village, with 57 cases, representing 20.21%. Based on data from the Tanjung Enim Community Health Center over the past three years, there were 252 cases recorded in 2023, representing 26%.The objective was to identify factors influencing pneumonia cases in toddlers in Tegal Rejo Village. The research method used a descriptive analytical design with a cross-sectional approach. The study population was all toddlers aged 12-59 months in Tegal Rejo Village. The sample in this study was all 110 toddlers in Tegal Rejo Village. The sampling technique used total sampling. The results showed a significant relationship between immunization status and the incidence of pneumonia in toddlers with a ρ value of 0.000. There was a significant relationship between the history of exclusive breastfeeding and the incidence of pneumonia with a value of ρ0.000. There was a significant relationship between residential density and the incidence of pneumonia in toddlers with a ρ value of 0.003. There was a significant relationship between smoking habits and the incidence of pneumonia in toddlers with a value of ρ 0.001. From the results of the study, the researchers concluded that immunization status, history of exclusive breastfeeding, residential density, and smoking habits were related to the incidence of pneumonia in toddlers in Tegal Rejo Village, Tanjung Enim Health Center Work Area in 2025. All health workers continue to provide information and counseling on the dangers of pneumonia to the community, such as the importance of providing exclusive breastfeeding, immunizing toddlers and the dangers of smoking in the home. Because this disease is very high risk and can be transmitted to family members at home.